Strategi Komunikasi Pemasaran Sosial dalam Penguatan Kesadaran Lingkungan melalui Program Ecolution di Kota Bekasi - -, Marlina; Nugraeni, Dunola Tri; Hamdani, Ayu Rakhmi Tiara (Ikatan Sarjana Komunikasi Indonesia, 2025)
Abstract - The Ecolution program, initiated by the LSPR Institute of Communication and Business, implements a social marketing communication strategy to enhance environmental awareness and foster public participation in household waste management in Bekasi City. This study employs a mixed-methods approach with an explanatory sequential design. Quantitative pre-and post-intervention surveys were conducted with 400 household heads across 10 sample sub-districts. Qualitative data were collected through 22 in-depth interviews with key stakeholders (government officials, academics, activists, and participants) and participatory observation. Data were analyzed using descriptive and inferential statistics (paired t-test) and thematic analysis with NVivo 12 software. The results indicate significant improvements in environmental knowledge (+28%), positive attitudes toward waste management (+21%), and waste-sorting practices, with an average increase of 12 kg per household per month. Qualitative findings identify three key success drivers: (1) locally framed messages based on community pride, (2) strategic multi-actor collaboration (triple helix), and (3) the use of digital and face-to-face channels for experiential learning. The analysis also shows that creative activities such as skincare waste banks, plogging, and photo competitions significantly boost youth engagement. The study concludes that the Ecolution model is an effective and replicable behavioral change communication framework. Policy recommendations include stakeholder adoption of the model, hybrid funding mechanisms, curricular integration, and the establishment of local green behavior communication units.Keywords: Ecolution; Social Marketing Communication; Environmental Awareness; Waste Management; Sustainable Behavior Abstrak - Program Ecolution yang diinisiasi oleh LSPR Institute of Communication and Business merupakan penerapan strategi komunikasi pemasaran sosial untuk memperkuat kesadaran lingkungan dan mendorong partisipasi publik dalam pengelolaan sampah rumah tangga di Kota Bekasi. Penelitian ini menggunakan pendekatan metode campuran (mixed-methods) dengan desain eksplanatoris sekuensial. Survei kuantitatif pra dan pasca-intervensi dilakukan terhadap 400 kepala rumah tangga di 10 kelurahan percontohan. Data kualitatif dikumpulkan melalui 22 wawancara mendalam dengan pemangku kepentingan kunci (pemerintah, akademisi, aktivis, dan peserta program) serta observasi partisipatif. Data dianalisis secara statistik deskriptif dan inferensial (uji-t berpasangan), serta analisis tematik dengan perangkat lunak NVivo 12. Hasil penelitian menunjukkan peningkatan signifikan pada pengetahuan lingkungan (+28%), sikap positif terhadap pengelolaan sampah (+21%), serta praktik pemilahan sampah dengan peningkatan rata-rata 12 kg per rumah tangga per bulan. Temuan kualitatif mengidentifikasi tiga faktor pendorong keberhasilan: (1) framing pesan berbasis nilai lokal dan kebanggaan komunitas, (2) kolaborasi strategis multi-aktor (triple helix), dan (3) pemanfaatan kanal digital dan tatap muka untuk pembelajaran eksperiensial. Analisis juga menunjukkan bahwa kegiatan kreatif seperti bank sampah skincare, plogging, dan kompetisi foto secara signifikan meningkatkan keterlibatan generasi muda. Studi ini menyimpulkan efektivitas model Ecolution sebagai kerangka komunikasi perubahan perilaku yang dapat direplikasi. Rekomendasi kebijakan mencakup adopsi model oleh pemangku kepentingan, pendanaan hibrida, integrasi kurikulum, serta pembentukan unit komunikasi perilaku hijau di tingkat daerah.Kata kunci: Ecolution; Komunikasi Pemasaran Sosial; Kesadaran Lingkungan; Pengelolaan Sampah; Perilaku Berkelanjutan.